(untitled) (European Journal of Social Science Education and Research, 2020)
In this paper, we started from the established view that the information technology has (IT) improved the education, regarding that it gives better results in students learning (Generation “Z”) as compared to traditional methods of work. The aim of this paper is to present the research results that we obtained. They show that students achieve better results by learning identical content in the traditional way (from the book), but using the technology. However, when the same material for students learning is offered in the form of thoughtful-appropriate and multimedia-interactive e-animated content with the direct manipulation, IT has claimed the advantage.